Uji Kuantitatif Kadar Protein pada Tempe Kedelai dan Lamtoro - Qurrotu A’yunin Lathifah; Andyanita Hanif Hermawati (Borneo Journal of Medical Laboratory Technology, 2019)
Food is the most essential requirement for humans to maintain life and living. One of the quality of food can be from nutrients contained in it. Efforts to diversify food can be done by finding new food ingredients or materials from existing food and developed into a diverse food material. The use of lamtoro seeds as the basis for making tempeh is one form of food diversification. Sampling in this study is Simple Random Sampling with a total sample of 2 soybean tempeh and 2 lamtoro tempeh. Research data collection using experiments. In this study, different results were obtained from each soybean tempeh and lamtoro tempeh.